Integrated Building Cells for a Simple Modular Design of Electronic Circuits with Reduced External Complexity: Performance, Active Element Assembly, and an Application Example - Šotner, Roman; Jeřábek, Jan; Polák, Ladislav; Prokop, Roman; Kledrowetz, Vilém (MDPI, 2019)
This paper introduces new integrated analog cells fabricated in a C035 I3T25 0.35-m ON Semiconductor process suitable for a modular design of advanced active elements with multiple terminals and controllable features. We developed and realized five analog cells on a single integrated circuit (IC), namely a voltage differencing differential buffer, a voltage multiplier with current output in full complementary metal–oxide–semiconductor (CMOS) form, a voltage multiplier with current output with a bipolar core, a current-controlled current conveyor of the second generation with four current outputs, and a single-input and single-output adjustable current amplifier. These cells (sub-blocks of the manufactured IC device), designed to operate in a bandwidth of up to tens of MHz, can be used as a construction set for building a variety of advanced active elements, offering up to four independently adjustable internal parameters. The performances of all individual cells were verified by extensive laboratory measurements, and the obtained results were compared to simulations in the Cadence IC6 tool. The definition and assembly of a newly specified advanced active element, namely a current-controlled voltage differencing current conveyor transconductance amplifier (CC-VDCCTA), is shown as an example of modular interconnection of the selected cells. This device was implemented in a newly synthesized topology of an electronically linearly tunable quadrature oscillator. Features of this active element were verified by simulations and experimental measurements.

This paper introduces new integrated analog cells fabricated in a C035 I3T25 0.35-m ON Semiconductor process suitable for a modular design of advanced active elements with multiple terminals and controllable features. We developed and realized five analog cells on a single integrated circuit (IC), namely a voltage differencing differential buffer, a voltage multiplier with current output in full complementary metal–oxide–semiconductor (CMOS) form, a voltage multiplier with current output with a bipolar core, a current-controlled current conveyor of the second generation with four current outputs, and a single-input and single-output adjustable current amplifier. These cells (sub-blocks of the manufactured IC device), designed to operate in a bandwidth of up to tens of MHz, can be used as a construction set for building a variety of advanced active elements, offering up to four independently adjustable internal parameters. The performances of all individual cells were verified by extensive laboratory measurements, and the obtained results were compared to simulations in the Cadence IC6 tool. The definition and assembly of a newly specified advanced active element, namely a current-controlled voltage differencing current conveyor transconductance amplifier (CC-VDCCTA), is shown as an example of modular interconnection of the selected cells. This device was implemented in a newly synthesized topology of an electronically linearly tunable quadrature oscillator. Features of this active element were verified by simulations and experimental measurements.
Integrated Building Cells for a Simple Modular Design of Electronic Circuits with Reduced External Complexity: Performance, Active Element Assembly, and an Application Example
Keywords: advanced active elements; CMOS; electronic control; circuit synthesis and design; oscillator; modular approach; advanced active elements; CMOS; electronic control; circuit synthesis and design; oscillator; modular approach